الصحة النفسية وعلاقتها بالاتزان الانفعالي عند المراهق اليتيم - بن إسماعيل رحيمة , (Scientific Journal of University of Benghazi, 2019)
The importance of Our study in trying to understand the concept of emotional balance and the need to enjoy it to return positively to the psyche of adolescents to achieve mental health in general, and enables us to study the theoretical and applied to the meaning of the variables considered to be important variables in the new studies. As for the goals are: To clarify the relationship of mental health emotional balance in the orphan teenager and recognize the impact of bilateral interaction between them. Use the mental health scale and the emotional balance measure to identify them and apply them to the study sample. Therefore, the problem of the study was formulated as follows: Is there a relationship between mental health and emotional balance in the orphaned adolescents? To answer the main question, we have developed the following hypotheses: - There is a relationship between mental health and emotional balance in the orphaned adolescents. - There are statistically significant differences in the levels of adolescent orphans on the mental health scale by sex variable. - There were statistically significant differences in the scores of the orphans on the emotional equilibrium scale by sex variable. The study sample consisted of (n = 26) an orphaned adolescent aged between 11 and 14 years, and was deliberately selected for research necessity. The study was also carried out by the Association of Muslim Scholars and Boras Al Kamali and Memon Ali in the state of Kalima. According to the nature of the study, the descriptive descriptive approach was chosen. This approach is reflected in the study of the relationship between the variables of the study. Two tools were used: the mental health scale of "Mohamed Mohamed Bayoumi Khalil" and the measure of the emotional balance of: "Adel Mohamed Mahmoud Justice." Statistical methods were used to obtain the results of the study: the T test, the Pearson correlation coefficient, the arithmetic mean and the standard deviation. Based on the findings of this study, the following results were obtained: - There is a positive correlation between mental health and emotional balance in the orphaned adolescents. - There were statistically significant differences in the scores of the adolescents on the mental health scale according to gender variable. - There were statistically significant differences in the scores of the adolescents on the scale of emotional balance according to gender variable.